Digital Transformation of MSMEs: Inclusion, Readiness, and Innovation Toward a Sustainable Economic Ecosystem - Sitorus, Sunday Ade; Siagian, Nalom; Steven, Orlando (Theoretical and Practical Research in Economic Fields, 2026)
This study investigates the correlation between digital readiness, digital inclusion, and digital transformation with business model innovation and local economic sustainability among culinary MSMEs in Medan City. Using a quantitative approach grounded in the TOE Framework and DEIM model, data was collected from 250 respondents via structured questionnaires and analyzed using SEM-PLS. The findings reveal that digital readiness and digital inclusion significantly influence innovation in business models. Furthermore, the digital business ecosystem acts as a mediating variable impacting sustainable economic development. Practical implications include formulating community-based digital empowerment strategies and inclusive policy interventions.